Evaluación de ajo, orégano y chochos como alternativas antiparasitarias en comparación con albendazol administrado a perros del albergue Canino Municipal Guaranda. - Saltos Villalva, Lorena Elizabeth (2020)
The present study evaluating garlic, orégano and chochos as antiparasitic alternatives compared to albendazole administered to dogs was developed at the Guaranda municipal shelter located in the industrial park sector in Negroyacu belonging to the Guanujo parish of the Guaranda canton, within the following objectives were proposed: to determine the presence of gastrointestinal parasites in dogs through laboratory tests such as the Faust flotation technique; treat intestinal parasitosis in canines by natural alternatives and determine the best dewormer in canines, for which a completely randomized block design and statistical analyzes were applied such as: adeva, for the separation of means the tukey test was used at 0.05% probability, the correlation and regression analysis, in addition to checking The Student t test was used, with the statistical program infostat the excel program was also used to build the database, tables and graphs. The variables under study were sex, race, age, weight, body condition, gastrointestinal parasites present, macroscopic stool examination, parasitic load before post treatment. After analyzing the results found, we have been able to conclude that garlic and orégano treatments presented a 100% parasitic prevalence unlike the chochos treatment that I present 50% and therefore it was determined that the best dewormer turns out to be albendazole with 33% of cases positive despite its solubility characteristic that limits its action in canines, but it should be noted that the deworming action of these botanical elements is not ruled out and it is recommended deepening their study either in the canine species or in other species.